THE EFFECT OF GREEN ACCOUNTING, COMPANY CHARACTERISTICS, OWNERSHIP STRUCTURE, AND GCG ON THE COMPANY'S PERFORMANCE IN THE STEEL SUB-SECTOR LISTED ON THE IDX - Tania, Tessa Eka (JEA17: Jurnal Ekonomi Akuntansi, 2024)
This study investigates the relationship between the use of Green Accounting, company characteristics, ownership structure, and the implementation of Good Corporate Governance (GCG) with company performance in the steel sub-sector on the Indonesia Stock Exchange (IDX). The research method uses a quantitative approach by collecting data from companies in the steel sub-sector listed on the IDX. The main variables considered in this study are Green Accounting practices, company characteristics, ownership structure, and factors related to the implementation of GCG. The results showed no significant effect on all hypotheses used